Update of the Phase III trial 'GRETA' of surgery and tamoxifen versus tamoxifen alone for early breast cancer in elderly women. (March 2015) - Mustacchi, Giorgio; Scanni, Alberto; Capasso, Imma; Farris, Antonio; Pluchinotta, Alfonso; Isola, Giulio
Background: In the Phase III 'GRETA' trial 474 women aged ≥70 years with early breast cancer were randomly assigned to surgery plus tamoxifen for 5 years or tamoxifen alone for 5 years. This is a long-term update.Patients & methods: Focusing on patients still alive in 2003, outcome end points has been recalculated.Results: Median distant metastases disease-free survival is longer with tamoxifen alone for 5 years; (48.8 vs 37.9 months; p = 0.009). No difference was found in distant metastases rate, disease-free survival, breast cancer and overall survival.Conclusion: Primary endocrine treatment until the the best response, followed by minimal surgery and prosecution endocrine treatment for 5–10 years is a suitable option for elderly breast cancer patients. Delayed surgery does not prejudice overall survival.